Praktik Bisnis Syariah pada UMKM Keripik Jamur 55 di Kelurahan Tempurejo, Tempurejo, Pesantren Kota Kediri - mahfudhotin, mahfudhotin; Novitasari, Marda; Febrian, M. Hanafi (Fakultas Tarbiyah IAIN Kediri, 2024)
The purpose of sharia business practices is to improve the quality of human resources for MSMEs and students with MSME digital marketing assistance in Kediri City, precisely on 55 mushroom chips and ensure business continuity. These activities are able to increase sales and profits, expand target markets, deep customer loyalty, and increased competitive advantage. The benefits obtained from this activity are for participants to gain knowledge and expertise in digital marketing with the aim of increasing production activities and product promotion. Increased product orders from a wider target market will also be obtained. The method used is Participatory Action Research (PAR). The results of the dedication can be concluded that this digital marketing is carried out so that 55 mushroom chip consumers increase and expand from various regions. Assistance in digital marketing uses social media such as WhatsApp, Instagram which will be filled with photos and videos of content from 55 mushroom chip products. Photos and videos of this content are in the form of the types of products provided by 55 mushroom chips, the process of making products, packing, and shipping the resulting products, and 55 mushroom chip profiles. Photos and videos of content are published on WhatsApp, Instagram social media accounts.